PENGARUH PENGGUNAAN PERMAINAN TRADISIONAL MADURA TERHADAP HASIL BELAJAR SISWA KELAS IV SDN PEJAGAN 1 BANGKALAN PADA MATA PELAJARAN IPAS MATERI GAYA - Riska Candrawati; Bagus Rahmad Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the significant effect of the implementation of Madurese Traditional Games on Student Learning Outcomes This study is quantitative with an experimental research type with a Quasi Experimental Design research design and using a Nonequivalent Control Group research design which means that the experimental sample or control sample is not selected randomly. The sample used in this study were 43 fourth-grade students of SDN Pejagan 1 Bangkalan. This study used an experimental class and a control class. Data collection techniques used were observation, questionnaires and multiple-choice tests. The trial of the test instrument used validity, reliability, and difficulty tests. Data analysis used normality and homogeneity tests, Hypothesis testing used independent sample t-test. Based on the results of the independent sample t-test data analysis on the post-test obtained a significance value of 0.001. According to the testing criteria, if the sig value (2-tailed) <0.05 then Ho is rejected and Ha is accepted, The results of the hypothesis test show that there is a significant difference in the implementation of Madurese Traditional Games on the Learning Outcomes of Fourth-grade Students of SDN Pejagan 1 Bangkalan in the Science Subject of Style Material.